Uso de principios de la arquitectura bioambiental integrada al paisaje en el diseño de un hotel 4 estrellas en Conache - Trujillo - Carranza Sotelo, Gianfranco Paul (2017)
In the design of a hotel in the area of Conache , architecture in this project will have to adapt , and search the landscape integration QE is a strategy of intervention in the territory that aims to guide the transformation of the landscape or correct those already made for get adapt to the landscape taken as a reference . More precisely , it will consist of adjusting an object or territorial action to the physiognomic characteristics of a given landscape, or some of its components , as well as their character and their semantic content. Thus , by integrating an object is inserted into a given landscape so that it tends to melt . There is, therefore , alteration, at least substantially , the existing landscape in reality. La Libertad located in the northern part of the country, has an annual income of visits 1.428 025 tourists, of which 65 % are left in the city , and 35% go to the surroundings (beaches, eyebrows jungles, field) . In 2012 , freedom , more specifically Trujillo, covered approximately 30% of annual national visits in the country, only behind Lima and Cusco The natural environment in the area of Trujillo , more specifically the countryside on the outskirts of the city , is not architectural elements which manage to take advantage of the immediate context. Recreational centers can be found mostly only 2 hotels and adequately trained for the public. Specifically in the area of Conache sector about 55 hectares , there is no type of hotel infrastructure.